A Suzuki Type Coupled Fixed Point Theorem for Generalized Multivalued Mapping - Pushpendra Semwal; Ramesh Chandra Dimri (Abstract and Applied Analysis)
We obtain a new Suzuki type coupled fixed point theorem for a multivalued mapping T from X×X into CB(X), satisfying a generalized contraction condition in a complete metric space. Our result unifies and generalizes various known comparable results in the literature. We also give an application to certain functional equations arising in dynamic programming.